Is Low Serum Klotho Level Associated with Alterations in Coronary Flow Reserve? - Keles, Nursen; Caliskan, Mustafa; Dogan, Burcu; Aksu, Feyza; Bulur, Serkan; Keles, Necibe Nur; Kostek, Osman; Aung, Soe Moe; Isbilen, Banu; Demircioglu, Kenan; Kalcik, Macit; Oguz, Aytekin (Echocardiography (Mount Kisco, N.Y.), 2016)
Background The Klotho gene, described as an “aging suppressor” gene, encodes a single‐pass transmembrane protein. The extracellular part of Klotho is cleaved and released into the circulation where it may function as a vasculoprotective hormone. Coronary flow reserve (CFR) is accepted as a marker of coronary microvascular dysfunction when epicardial coronary stenosis is absent. There are no data regarding the relationship between serum Klotho levels and disorders in coronary microcirculation in healthy adults. We aimed to investigate the association between serum Klotho levels and alterations in coronary microcirculation in healthy adults using echocardiographic measurements of CFR. Methods Thirty‐four healthy volunteers (median age: 34 [27–39], 14 males) were enrolled in this study. The study population was divided into two subgroups according to the median value of serum Klotho levels: a high Klotho (HK) group (n = 17, median age: 34 [30–38]; 6 males) and a low Klotho (LK) group (n = 17, median age: 32 [26–39]; 8 males). The analysis of coronary flow velocities was performed by transthoracic Doppler echocardiography. Results Hyperemic diastolic peak flow velocities and CFR were significantly higher in the HK group than in the LK group (70 [66–92] versus 61 [47–66], P = 0.003 and 3.0 [2.6–3.8] versus 2.2 [1.7–2.8], respectively, P = 0.001). Serum Klotho levels were positively correlated with CFR (P < 0.001). Conclusion Serum Klotho levels correlate with CFR in a healthy population. Low serum Klotho levels may potentially identify patients with impaired CFR.